The Current Condition of Coral Reef and Fish Diversity in Gosong Island, Southwest Aceh - Nurul Najmi; Ananingtyas S. Darmarini; Nanda Muhammad Razi; Mai Suriani; Samsul Kahar (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research